The Impact of Unhealthy Relationships Among Co-Workers on Employees’ Performance and Organizational Commitment - Ordinaria, Shiera May (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the impact of unhealthy relationships among co-workers on employee performance and organizational commitment among non-teaching personnel of Jose Rizal Memorial State University–Katipunan Campus during School Year 2025–2026. Anchored on Social Exchange Theory (SET), Affective Events Theory (AET), and the Job Demands-Resources (JD-R) Model, the study explored how workplace interpersonal dynamics relate to employee outcomes. A descriptive-correlational research design was employed involving 109 non-teaching personnel selected through total enumeration. Data were gathered using an adapted questionnaire-checklist that assessed unhealthy workplace relationships in terms of workplace conflict, gossip and backstabbing, lack of trust, poor communication, and bullying or harassment; employee performance in terms of work quality, productivity, efficiency, and task completion; and organizational commitment in terms of affective, continuance, and normative commitment. The instrument underwent validation and reliability testing, while data were analyzed using mean, standard deviation, and Spearman rank correlation through Jamovi software. Findings revealed that unhealthy workplace relationships were manifested at an average level, with gossip and backstabbing and poor communication identified as highly evident concerns, while workplace conflict and lack of trust were moderately manifested and bullying or harassment occurred at a low level. Despite these workplace concerns, employees demonstrated a high level of performance across all indicators, including work quality, productivity, efficiency, and task completion. Organizational commitment was generally average, with affective commitment rated high, while continuance and normative commitment were rated average. Results further showed that unhealthy relationships among co-workers had no significant relationship with employee performance (r = 0.033, p = 0.735) and organizational commitment (r = 0.068, p = 0.479). The study concluded that unhealthy workplace relationships did not significantly influence employee performance and organizational commitment, suggesting that other organizational and personal factors may contribute to employee outcomes. The study recommends strengthening workplace relationships through improved communication, conflict resolution initiatives, employee development programs, and supportive human resource policies. The study supports Sustainable Development Goal 16 (Peace, Justice and Strong Institutions) by promoting respectful, inclusive, and accountable workplace environments. It also contributes to institutional sustainability by providing insights that may guide organizations in developing policies and practices that enhance workplace well-being, employee engagement, and organizational effectiveness.
Keywords: Employee Performance; Organizational Commitment; Organizational Behavior; Unhealthy Workplace Relationships; Workplace Conflict